Kant, the European Commission, and the Unity of Reason: Relevance and Irrelevance of the Distinction Between the Moral Politician and the Political Moralist as the Keystone of the Critical Saga - Sánchez Domínguez, Antonio (Con-Textos Kantianos. International Journal of Philosophy, 2025)
The text examines the Treaty of Rome’s (1957) decision to designate the European executive body as the “Commission,” replacing the ECSC’s “High Authority.” It argues that this ostensibly bland, technical naming sought to avoid the appearance of supranational sovereignty while at the same time installing technocratic grammar that depoliticizes power. In light of Schmitt and Heidegger, it questions the alleged neutrality of technique and its capacity to conceal political decisions under the veil of the “technical.” The guiding thread is Kant: the distinction between the technical-practical and the moral-practical, and between the “moral politician” and the “political moralist.” Only the primacy of the moral-practical —of laws grounded in freedom, with every decision arising from natural determinations bracketed— can limit politics and orient the State toward perpetual peace; technical prudence yields management, cunning, and simulation. Applied to Europe, calling the executive a “Commission” would have been a ploy that predisposes the Union to the hegemony of technique, weakening transparency and even the possibility of understanding cosmopolitan right as a mandate. The essay concludes that this drift favors nihilism and civic disaffection: without a rearticulation of the unity of reason and of the person’s place, the institutional machinery becomes gearwork without a horizon.